2010
DOI: 10.1292/jvms.09-0517
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Cross-Immunity of Eimeria Species on Korean Chicken Farms

Abstract: ABSTRACT. Epidemiology of Eimeria species in poultry flocks is important to increase the effectiveness of vaccinations and prophylactic strategies on chicken farms. In this study, fecal samples from 356 chicken farms were collected randomly and examined for the prevalence of Eimeria species. Through microscopic examination, it was determined that 78.7% of the tested farms were positive in Eimeriainfection. Seven Eimeria species were detected in all the positive farms by PCR amplification of the internal transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 23 publications
8
41
1
Order By: Relevance
“…The number of oocysts appears to be a limiting factor for identication through PCR. Lee et al (2010) used 50 oocysts for individual amplifications. Fernandez et al (2003b) found a minimum limit of 50 oocysts for detection of six species using the PCR multiplex, while the limit for E. tenella was found to be 100 oocysts both in individual and multiplex reactions.…”
Section: Dicussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of oocysts appears to be a limiting factor for identication through PCR. Lee et al (2010) used 50 oocysts for individual amplifications. Fernandez et al (2003b) found a minimum limit of 50 oocysts for detection of six species using the PCR multiplex, while the limit for E. tenella was found to be 100 oocysts both in individual and multiplex reactions.…”
Section: Dicussionmentioning
confidence: 99%
“…According to Conway et al (1993), only 100 E. acervulina and E. tenella oocysts are needed to cause serious gastrointestinal disorders in birds. Furthermore, molecular diagnosis can accurately reveal the prevalence of Eimeria species, thus contributing to the strategic employment of medicines and vaccines (Sun et al, 2009;Lee et al, 2010).…”
Section: Dicussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence and identification of Eimeria species are useful tools for prevention and control of coccidiosis [4]. The prevalence may vary from less than 10 % to more than 90 % in broilers worldwide [5,6,7,4].…”
Section: Introductionmentioning
confidence: 99%
“…Occurrences of coccidiosis in commercial poultry can range from 5 to 70% (DU;HU, 2004;FREITAS et al, 2008;AARTHI et al, 2010;LEE et al, 2010;TOLEDO et al, 2011), and economic losses have been widely reported (DALLOUL; LILLEHOJ, 2006).…”
Section: Introductionmentioning
confidence: 99%